Global Forces Shaping the Textile and Clothing Industry in the 21st Century - Panych, Daria (2024)
This bachelor's thesis investigates global crises' impacts on the Textile and Clothing industry, including the Great Recession, the Trade War between the USA and China, the COVID-19 Pandemic, and Relocation Shocks. The research question focuses on how these global events affect the performance and adaptability of the industry. Did these events contribute to growth and innovation, or did they hinder progress instead? The first chapter offers a historical perspective on the development of the textile and apparel sector, focusing on the manufacturing and distribution processes. The second chapter examines in detail the individual events that have impacted the industry and evaluates their specific effects on various aspects. The third chapter includes a case study of Ralph Lauren, including a qualitative interview and analysis of the company's annual reports, to understand better how the company manages obstacles and seizes opportunities during times of crisis. The thesis aims to analyze how global crises affect employment, production, and global supply chains in the industry. It also assesses the industry's ability to innovate and adapt in response to these crises. The methodology includes case studies, analyses of secondary data, literature, and statistical data, which allow for the assessment of the macroeconomic impacts on the garment industry. The research includes an analysis of the consequences, market changes, and sector adaptation. The study offers a new perspective on the adaptation and resilience of the Textile and Clothing industry to global challenges.